The Role of Inflammation in the Treatment of Schizophrenia - Fond, Guillaume; Lançon, Christophe; Korchia, Theo; Auquier, Pascal; Boyer, Laurent (Frontiers in Psychiatry, 2020)
Background. Inflammation plays a major role in the onset and maintenance of schizophrenia. The objective of the present work was to synthetize in a narrative review the recent findings in the field of inflammation in schizophrenia and their application in daily practice. Method. This review was based on the most recent meta-analyses and randomized controlled trials. Results. The disturbed cytokines depends on the phase of the illness. A meta-analysis of cytokines in schizophrenia found higher levels of proinflammatory and anti-inflammatory cytokines in the peripheral blood in both patients with first-episode schizophrenia and relapsed patients than in healthy controls. Exploring detailed data on immune-inflammatory disturbances in SZ reveals that IL-6 is one of the most consistently disturbed cytokine in SZ. Other cytokines including IL1, TNF and IFN are also disturbed in schizophrenia. Choosing a broad-spectrum anti-inflammatory agent that may inhibit subsequent pathways may be particularly useful for the treatment of inflammatory schizophrenia. Highly sensitive-C-Reactive Protein is a useful screening marker to detect inflammation in SZ subjects. Anti-inflammatory agents have shown effectiveness in the recent published meta-analyses. Only one study found a significant difference between celecoxib and placebo but two found a trend toward significance on illness severity and one on positive symptoms. In addition, other published and unpublished data was included in another meta-analysis that concluded to a significant effect of add-on celecoxib in positive symptoms in first episode patients. There is a lack of data to determine if aspirin is truly effective in schizophrenia to date. Other anti-inflammatory agents have been explored including hormonal therapies, antioxidants, omega 3 fatty acids and minocycline showing significant effects for reducing total, positive and negative scores symptoms and general functioning. However, each of these agents has multiple properties beyond inflammation and it remains unclear how these drugs improve schizophrenia. Conclusion. The next step is to tailor anti-inflammatory therapy in schizophrenia, with two main challenges: 1. To provide a more efficient anti-inflammatory therapeutic approach that targets specific pathways associated with the pathology of schizophrenia. 2. To develop a more personalized approach in targeting patients who have the best chance of successful treatment.